Information acquisition in vertical relations - Pio Baake; Andreas Harasser; Friederike Heiny (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
We analyze a simple supply chain with one supplier, one retailer and uncertainty about market demand. Focusing on the incentives of the supplier and the retailer to enhance their private information about the actual market conditions, we show that choices on information acquisition are strategic complements. While the retailer's incentives are mainly driven by the information rent that he can earn, the supplier will choose to acquire information only if the retailer is rather well informed, even though the information is free of charge.
Keywords: D82; D83; D86; 330; asymmetric information; information acquisition; vertical relations